Pedometer and biochemistry monitoring on postoperative from Nelore cattle with umbilical diseases - Teodoro, P. H. M. [UNESP]; Silva, J. R. B. [UNESP]; Santos, P. S. P. [UNESP]; Viana Filho, M. N.; Alves, A. L. G. [UNESP]; Hussni, C. A. [UNESP]; Watanabe, M. J. [UNESP]; Rodrigues, C. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Postoperative analgesia in cattle is sometimes overlooked, frequently due to the lack of quantitative methods for diagnosis and measurement. The objectives of this study were: to analyze the pedometric and biochemistry alterations of postoperative period in Nelore bovines with umbilical diseases; compare the anti-inflammatory and analgesic efficiency between different doses of flunixin meglumine and meloxicam in the postoperative of umbilical diseases in these animals. Twenty four bovines were used. From this total, 18 animals were submitted to laparotomy for treatment of umbilical diseases and subsequently divided into three groups of animals: G1, which received 1.1mg/kg flunixin, G2 2.2mg/kg flunixin, G3 0.5mg/kg meloxicam. Six other healthy cattle were allocated to the control group (CG). Total blood samples for plasma cortisol clinical examination was performed on standardizer times. Plasma cortisol concentrations differed only in the M0 between GC and treated groups. Flunixin meglumine in different doses and meloxicam were equivalent in the treatment of postoperative pain and anti-inflammatory effect in cattle submitted to laparotomy for the treatment of umbilical diseases.
Keywords: pedometric; flunixin meglumine; meloxicam; umbilical diseases; calves